1995
DOI: 10.1523/jneurosci.15-11-07105.1995
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic, GABAergic, and glutamate-enriched inputs from the mesopontine tegmentum to the subthalamic nucleus in the rat

Abstract: In order to clarify the origin and to examine the neurochemistry and synaptology of the projection from the mesopontine tegmentum (MTg) to the subthalamic nucleus (STN), rats received discrete deposits of anterograde tracers in different regions of the MTg. Anterogradely labeled fibers were examined in the light and electron microscopes. The distribution of GABA or glutamate immunoreactivity was examined by post- embedding immunocytochemistry. The anterograde tracing demonstrated that the projection to the STN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
114
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(121 citation statements)
references
References 69 publications
7
114
0
Order By: Relevance
“…The synapse types formed by cholinergic terminals in the VTA are also likely to reflect the colocalization of other transmitters in these axons, in particular glutamate and GABA (Bevan and Bolam, 1995;Clarke et al, 1997;Jia et al, 2003). Our observation of GABA immunoreactivity in some cholinergic terminals in the VTA is consistent with these findings.…”
Section: Cholinergic Terminals Within the Vtasupporting
confidence: 87%
“…The synapse types formed by cholinergic terminals in the VTA are also likely to reflect the colocalization of other transmitters in these axons, in particular glutamate and GABA (Bevan and Bolam, 1995;Clarke et al, 1997;Jia et al, 2003). Our observation of GABA immunoreactivity in some cholinergic terminals in the VTA is consistent with these findings.…”
Section: Cholinergic Terminals Within the Vtasupporting
confidence: 87%
“…This type of synapse is typical of ␥-aminobutyric acid (GABA)ergic terminals (Sotelo et al, 1986;Schander et al, 1987;Onteniente et al, 1987;Bevan and Bolam, 1995;Sesack and Pickel, 1995). In this regard, light microscopic studies have shown the presence of GABA-containing boutons surrounding the somata and dendrites of PPT/LDT cholinergic cells (Ford et al, 1995).…”
Section: Noncholinergic Inputs To Cholinergic Neuronsmentioning
confidence: 95%
“…Noncholinergic neurons that contain GABA (Mugnaini and Oertel, 1985;Ford et al, 1995) or glutamate (Clements et al, 1991;Lavoie and Parent, 1994a) are known to exist in the PPT/LDT region of the rat. Tracing studies combined with immunocytochemistry have shown that glutamatergic mesopontine cells innervate the subthalamic nucleus (Bevan and Bolam, 1995) and the substantia nigra (Lavoie and Parent, 1994a;Charara et al, 1996). These glutamatergic projections to the basal ganglia nuclei are believed to be involved in the control of movement, in both physiological and pathological conditions (Inglis and Winn, 1995;Winn et al, 1997).…”
Section: Presynaptic Vachtmentioning
confidence: 99%
“…This site was chosen because a review of the literature showed that the region of the PPTn from its caudal border with the parabrachial complex to the nearest coronal section at which the decussation of the superior cerebellar peduncle is fully elaborated has the necessary connectivity to modulate REM sleep and its respiratory phenotype. This caudal pole of the PPTn is neurophysiologically distinct, since unlike more rostral PPTn locations, neurons in this caudal region are REM sleep-active, project to the PRF (Jones, 1990;Semba et al, 1990;Semba and Fibiger, 1992;Kohlmeier et al, 2002) and thalamus (Semba et al, 1990;Semba and Fibiger, 1992;Bevan and Bolam, 1995), and are thought to modulate REM sleep and the associated electrocortical activation (Steriade and McCarley, 2005a,b). Neurons in the caudal pole of the PPTn also project to the areas of the rostral ventrolateral medulla (Yasui et al, 1990) that contain respiratory neurons critical to the generation of respiratory rhythm and pattern (Feldman and Del Negro, 2006), and to motor pools such as the hypoglossal motor nucleus which innervates the genioglossus muscle of the tongue (Woolf and Butcher, 1989;Fay and Norgren, 1997;Rukhadze and Kubin, 2007).…”
Section: Anesthesia and Surgical Proceduresmentioning
confidence: 99%